2012
DOI: 10.19030/iber.v11i5.6972
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency Of Intellectual Capital Investments As A Potential Leading Indicator

Abstract: This paper aims to test the VAIC model in order to explore and recognize the relationship between Intellectual Capital (IC) components and the financial performance of companies, with an ambition to establish whether IC investment efficiency indicators can serve as potential leading indicators of the future financial performance of companies. We test our hypotheses by using the VAIC model. The data set includes more than 12,000 Slovenian companies within a 14-year period (from 1995 to 2008). OLS regression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…So far, researchers have investigated the relationship among VAIC™-based measures and overall performance measures (such as ROA, ROE etc.) with inconsistent results (Javornik et al 2012;Iazzolino and Laise 2013). Thus, additional research is necessary to further clarify these results.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…So far, researchers have investigated the relationship among VAIC™-based measures and overall performance measures (such as ROA, ROE etc.) with inconsistent results (Javornik et al 2012;Iazzolino and Laise 2013). Thus, additional research is necessary to further clarify these results.…”
Section: Discussionmentioning
confidence: 98%
“…Whereas some of the results are ambiguous (Javornik et al 2012;Iazzolino and Laise 2013), many studies have confirmed positive relationship of intellectual capital and firm performance (e.g. Chen et al 2005;Clarke et al 2011;Alipour 2012;Mondal and Ghosh 2012;Pilkova et al 2013;Holienka and Pilkova 2014).…”
Section: Intellectual Capital and Value Creation In Smesmentioning
confidence: 99%
“…[10]. This research are different with [11]. As IC value Advances in Social Science, Education and Humanities Research, volume 409 is a result of above-average financial performance, the IC investment efficiency can potentially serve as leading indicators of future financial performance 2) Effect of Intellectual Capital on financial performance with Islamic work ethics as moderating variables: Based on the results of the MRA regression calculation the regression coefficient values for the Interaction of Intellectual Capital (IC) and Islamic Work Ethics (IC.EKI) (β3) amounting to -0,000257.…”
Section: ) Effect Of Intellectual Capital On Performancementioning
confidence: 66%
“…According to the Slovenian Companies Act (ZGD-1) in force during the 13 Few others studies (Nemec Rudež & Mihalič, 2007;Jerman et al, 2010;Javornik et al, 2012;Jerman, 2013) examined period of time, the annual reports of all large and medium-sized capital companies, dual companies and those small capital companies whose securities are traded on the regulated market had to be audited and submitted to AJPES to be available to general public…”
Section: Methodology Samplementioning
confidence: 99%